Several medicinal plants species which need enrichment planting - Agus Ismanto; Andianto Andianto; Rossi Margareth Tampubolon (Scripta Biologica, 2019)
Pulai (Alstoniasp.), Kayumanis/Cinnamon (Cinnamomum burmanii, Cinnamomum iners), Pakanangi/Kisereh (Cinnamomum parthenoxylon/Cinnamomum porrectum), Kulilawang (Cinnamomum halmaherae), Agarwood (Aquilaria sp., Gyrinops versteeghii and Gyrinopsis cumingiana), and Pasakbumi (Eurycoma Longifolia) are some of  medicinal plants species which growing in plantation or natural forest. The exploitation to these species causes their existence to be scarce or almost not known, with the result that is needed a policy to save the existence of medicinal plants species. Industries of herbal medicine which exploit the raw material from nature need to build seedlings and enrichment area. The collaboration between medicinal industries with local people to build medicinal plants species plantation can be developed. This paper informs a field review of some medicinal plants species from several regions during the research activities in 2005 to 2009.